1991
DOI: 10.1007/bf01055559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic exposure to sublethal concentrations of lead acetate on heme synthesis and immune function in red-tailed hawks

Abstract: Red-tailed hawks were exposed to sublethal levels of lead acetate for periods of 3 or 11 weeks. Alterations in the heme biosynthetic pathway were demonstrated after the first week of exposure to 0.82 mg lead per kilogram body weight per day. Activity of erythrocyte porphobilinogen synthase (aminolevulinic acid dehydratase) was depressed significantly and did not return to normal levels until 5 weeks after the termination of lead treatments. A rapid and relatively brief increase in erythrocyte free protoporphyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 14 publications
4
31
0
1
Order By: Relevance
“…Lead acetate treated group (T1) significantly (P<0.001) decreased red blood cell counts, hemoglobin levels and hematocrit values. Similar findings have been previously reported by Redig (1991). Development of anemia in lead toxicity may be attributed to the decreased red blood cell survival time because of the increased membrane fragility, reduced RBC count, decreased hemoglobin content or summation of all these factors (ATSDR, 1993).…”
Section: Effect Of Garlic On Serum Cholesterol In Lead Toxicity Inducsupporting
confidence: 85%
“…Lead acetate treated group (T1) significantly (P<0.001) decreased red blood cell counts, hemoglobin levels and hematocrit values. Similar findings have been previously reported by Redig (1991). Development of anemia in lead toxicity may be attributed to the decreased red blood cell survival time because of the increased membrane fragility, reduced RBC count, decreased hemoglobin content or summation of all these factors (ATSDR, 1993).…”
Section: Effect Of Garlic On Serum Cholesterol In Lead Toxicity Inducsupporting
confidence: 85%
“…The median blood lead level detected at the time of death from individuals that died due to lead poisoning was 150 ÎŒg/dL (n = 9; range = 80-523 ÎŒg/dL). Gochfeld, 2005;Kelly and Kelly, 2005), immunity (Redig et al, 1991;Snoeijs et al, 2004), and physiology (Carpenter et al, 2003;Finkelstein et al, 2012;Gangoso et al, 2009). Sublethal effects of lead and its contributing effects on mortality and population viability in wild bird populations are likely more prevalent than we are able to determine from studies of free-flying populations.…”
Section: Threats To Survivalmentioning
confidence: 77%
“…It has been suggested that lead may induce the production of Zn-binding proteins (e.g., Zn-protoporphyrin and delta-aminolevulinic acid), rendering zinc unavailable for accumulating in feathers (Redig et al 1991). Although zinc levels in the feathers of M. apiaster from the contaminated site were lower than most values reported in literature, it is unlikely that this is due to such phenomenon, since the level of zinc was also low in the pellets from the contaminated site (Table 1).…”
Section: Resultsmentioning
confidence: 99%